Halal culinary: opportunity and challenge in Indonesia - Prabowo, Sulistyo; Abd Rahman, Azmawani; Ab Rahman, Suhaimi; Abu Samah, Asnarulkhadi; Che Man, Yaacob (2012)
Halal business trends point to growing awareness consumption of halal products and services. The conventional concept of halal services extends to other fields beyond food and beverages. Tourism and hospitality sector shows demand for halal services, in which halal concern in hotels, restaurants, fast food, food stall and other culinary services have not showing priority for the issue. Service owners are not able to warrant for halal products, while majority of consumers are muslims. This article intends to review the causative problems resulting under development of halal certification in Indonesia.